Does Transcatheter Aortic Valve Implantation for Aortic Stenosis Impact on Cognitive Function?. Issue 3 (May 2020) - Gu, Sophie; Coakley, Daniel; Chan, Danny; Beska, Benjamin; Singh, Fateh; Edwards, Richard; Kunadian, Vijay
Abstract : Aortic stenosis (AS) is the most common valvular heart disease among elderly patients in developed countries. Surgical valve replacement is indicated for severe AS to relieve the obstructed outflow tract. Transcatheter aortic valve implantation (TAVI) has emerged as an alternative for patients with severe AS, particularly in those with high surgical risk. TAVI is a less invasive approach with favorable survival outcomes in high-risk patients compared with open surgery. Despite the remarkable success of TAVI, there is a growing concern on the incidence of postprocedural cognitive impairment. This review aims to evaluate the incidence of cognitive impairment following TAVI and to identify the potential contributing factors.